Tribological characterisation of magnetron sputtered Ti(C, O, N) thin films. (2nd August 2010) - Olteanu, C.; Munteanu, D.; Ionescu, C.; Munteanu, A.; Chappe, J.M.; Cunha, L.; Vaz, F.
Ti(C, O, N) thin films were prepared by magnetron sputtering and analysed in terms of their tribological properties. Surface and tribological parameters were analysed and discussed as a function of the films composition and structural features, as well as their thickness. The evolution of friction coefficient values was in concordance with the wear behaviour of the films. According to the atomic composition of the films, an increasing of the carbon percentage and a compound chemical formula closed to the stoichiometric TiC lead to a very good wear behaviour. This aspect is also directly correlated with the friction behaviour.